Men and Women in Marriage and Beyond: An Analysis of Phrase Usage in Media Texts - E. A. Bespalova (Научный диалог)
The article is   dedicated   to   the   analysis of the usage of phraseological units related to marriage in contemporary media texts. The material was extracted from the Russian National Corpus. The aim of the research is to identify the standard and new meanings and functions of phraseological units in this group in relation to the value orientations of contemporary Russian language speakers. The relevance of the study is determined by its linguistic-pragmatic and axiological orientation. The conducted analysis indicates that family continues to be a significant value for representatives of Russian linguistic culture. Society’s attitude towards the topic of marriage is traced within the framework of phraseological blocks, which depict (1) the position of men and women before entering into marriage, (2) within the marital union (this taxon is represented by the largest number of phraseological units), (3) outside of marriage. At the same time, expressions related to civil marriage also emerge in frequent positions. It is shown that euphemistic expressions for infidelity are more often associated with male actors. Media texts demonstrate the development of views on traditional roles of men and women, as well as the presence of non-traditional forms of marriage. Phraseology related to marriage is actively used metaphorically in relation to various spheres of societal life: politics, economy, sports, etc.